The potential benefits of citizen science for spatial planning: an exploratory analysis of 22 Belgian and Dutch cases - Goosse, Tom; Lamker, Christian; Devos, Tim (European planning studies, 2025)
Citizen science is gaining attention for its innovative potential for research, policy-making, and address spatial aspects of sustainability transitions. However, spatial planners struggle to harness this potential beyond the extension of participatory processes. Approaches seek to recognize citizens views alongside governmental expertize in communicative processes, while citizen science is rarely conceptualized through lenses of co-production and self-organization. This paper explores the potential benefits of citizen science for spatial planning along emerging and potential interfaces. Drawing on a literature review focussed on spatial planning and citizen science, we examine existing typologies and analyse 22 citizen science cases from Flanders (Belgium) and the Netherlands that engage with spatial issues. The study identifies four types of interfaces between citizen science and spatial planning practices, highlighting diverse ways in which citizen science can inform or support participatory planning processes. It opens the potential for various societal actors to engage with a citizen science project, form collaborations and develop new role distributions within spatial planning.